Motivation and affordance: A study of graduate students majoring in translation in China - Wang, Xiaochen; Sun, Fei; Wang, Qikai; Li, Xinyu (Frontiers in Education, 2022)
Many Chinese students further their master's study in translation, however, only a few of them become translators at last and most of them gradually decrease their language learning motivation in the translation program. Based on Complex Dynamic Systems Theory, the study adopted a sequential mixed methods design with both questionnaires and interviews to collect the data. We collected 446 questionnaires to explore what types of affordances influence their language learning motivation most. After that, we interviewed six participants to explore how these affordances influence their motivation. Findings from the questionnaires showed that the affordances of the mentor can be divided into strong academic ability, rich academic resources, caring students, and strict requests; affordances of the instructor can be divided into informative courses, being serious in class, strong teaching ability, practical courses, new teaching methods, and the reasonable course planning; affordances of the peer can be divided into peer pressure, shared learning resources, mutual encouragement and mutual supervision. Affordances of the institution can be divided into a good learning atmosphere, sufficient internship opportunities, abundant library resources, good infrastructure, and scholarships. Findings from the interview showed that different interpretations of affordances lead to different effects on language learning motivation; affordance has little influence on intrinsic language learning motivation. This study provided some insights for policymakers and teachers on how to cultivate and promote translation students’ language learning motivation.